BAY 41-2272, a soluble guanylate cyclase agonist, activates human mononuclear phagocytes - Soeiro-Pereira, PV (Blackwell Publishing Ltd, 2012)
BACKGROUND AND PURPOSE: Phagocyte function is critical for host defense against infections. Defects in phagocytic function lead to several primary immunodeficiencies characterized by early onset of recurrent and severe infections. In this work, we further investigated the effects of BAY 41-2272, a soluble guanylate cyclase (sGC) agonist, on the activation of human peripheral blood monocytes (PBM) and THP-1 cells. EXPERIMENTAL APPROACH: THP-1 cells and PBM viability was evaluated by methylthiazoletetrazolium assay; reactive oxygen species production by lucigenin chemiluminescence; gene and protein expression of NAPDH oxidase components by qRT-PCR and Western blot analysis, respectively; phagocytosis and microbicidal activity by co-incubation, respectively, with zymosan and Escherichia coli; and cytokine release by elisa. KEY RESULTS: BAY 41-2272, compared with the untreated group, increased spreading of monocytes by at least 35%, superoxide production by at least 50%, and gp91(PHOX) and p67(PHOX) gene expression 20 to 40 times, in both PBM and THP-1 cells. BAY 41-2272 also augmented phagocytosis of zymosan particles threefold compared with control, doubled microbicidal activity against E. coli and enhanced the release of TNF-α and IL-12p70 by both PBM and THP-1 cells. Finally, by inhibiting sGC with ODQ, we showed that BAY 41-2272-induced superoxide production and phagocytosis is not dependent exclusively on sGC activation. CONCLUSIONS AND IMPLICATIONS: In addition to its ability to induce vasorelaxation and its potential application for therapy of vascular diseases, BAY 41-2272 was shown to activate human mononuclear phagocytes. Hence, it is a novel pro-inflammatory drug that may be useful for controlling infections in the immunocompromised host.